Estrogen regulates forkhead transcription factor 2 to promote apoptosis of human ovarian granulosa-like tumor cells. Issue 194 (November 2019) - Wu, Jun; Miao, Chunlei; Lv, Xiaoyu; Zhang, Yujie; Li, Yanyan; Wang, Di
Highlights: FOXL2 is highly expressed in KGN cells and GCT tissues. FOXL2 inhibits E2 synthesis, while E2 up-regulated the FOXL2 expression in KGN cells. Estrogen induces FOXL2 phosphorylation via GPCR-PKC non-genomic pathway. Estrogen promotes cell apoptosis via FOXL2. Abstract: Granulosa cell tumors of the ovary (GCTs) are the predominant form of ovarian stromal tumors and can lead to abnormally secreted estrogen hormones. Studies have reported that forkhead transcription factor 2 (FOXL2) inhibits estrogen synthesis and its gene mutation can lead to GCTs. We unexpected found that estrogen also regulates the expression level of FOXL2. High-dose estrogen increased the expression of FOXL2 in ovarian-like granulosa (KGN) cells at both the mRNA and protein levels. However, no research has reported on the molecular regulatory mechanism and function between estrogen and FOXL2 in the development of GCTs. In this research, FOXL2 was highly expressed in KGN cells and ovarian stromal tumor tissues. Deletion of FOXL2 increased the estrogen secretion in KGN cells. In turn, high-dose estrogen increased the FOXL2 expression levels. FOXL2 was phosphorylated by GPR30 (G protein coupled receptor)-Protein kinase C (PKC) signaling pathway upon estrogen stimulation. Estrogen inhibited cell migration and proliferation, while promoting cell apoptosis. Deletion of FOXL2 inhibited the influence of estrogen on cell proliferation, migration, and apoptosis. Results suggest that estrogen via regulating FOXL2 suppresses cell proliferation and induces cell apoptosis.